Sustainable Tourism: Conceptual Clarity and Contextualization in Nepal - Gautam, Biranji (Janapriya Journal of Interdisciplinary Studies, 2021)
Considering the paucity of empirical research, the purpose of the paper is to communicate the conceptual facets and empirical frameworks of sustainable tourism that can be contextualized in the context of Nepal. This paper is an analytical review, building on previous view. Empirical evidences, Systematic open discourse among stakeholders, Pragmatism Philosophy, Sustainable Mindset, Destination exploration and branding, Industry-Community-Government interrelationship, learning from best practices are prerequisites of initiating and implementing sustainable tourism practices in Nepal. Sustainability tourism is result of continuous efforts. The academic and business model depends upon context and mindset. This study attempts to offer some empirical models that can be contextualized in Nepalese context. In Nepalese context, revival and exploration of new destinations is needed before sustainability dimension. The research paper has suggested some of the research issues and models in which future research on Nepalese perspective could be conducted. Moreover, study has disseminated contextual remedies for initiating and implementing sustainable tourism scenario in Nepal.